Transition phase of connectivity for wireless networks with growing process. (14th November 2012) - Gu, Bo; Hong, Xiaoyan
The connectivity of wireless network is critical for effective and efficient communications. Yet, it is challenged by mobility, transmission range and density. In terms of increasing node density, there is a transition phase of connectivity when a network starts transforming from partition to connected state. In this paper, we study the upper– and lower–bounds of critical density for the transition phase using percolation theory. We further derive critical time points for the bounds according to three growth functions of node density. The simulation demonstrates the evolution of network connectivity and validates the connectivity transition times.